Storytelling One Day One Book Terhadap Kemampuan Bahasa Ekspresif Anak Usia 4-5 Tahun - Erna Budiarti; Dian Farista; Diana Indah Palupi; Ludgardis Wonga Wara; Siti Agustiani Rubiah; Umi Harti (Publikasi Indonesia, 2022)
Early childhood, which has an age range between 0-8 years, is a golden age, so it is very appropriate if stimulation is given according to the stages of their age and development, through storytelling it will make children try to remember all the components in the story, starting from the characters to the plot. stories and moral values contained therein. stimulate children to practice remembering by retelling the whole story using their own words so that their expressive language development can develop optimally. Early childhood education is the main foundation in developing the quality of human resources. Through language humans can relate to each other, can share experiences, learn from each other, and improve intellectual abilities. Children will experience difficulties in learning through play if they do not have enough language skills. Language is the main capital in the effort to get information and communicate in life. The method used in this study is a qualitative descriptive research method which aims to determine the development of expressive language skills in children aged 4-5 years through one day one book storytelling in ABA 72 Kindergarten. The research was conducted from 05-23 September 2022 as many as 3 cycles with a sample of 15 students from group A Kindergarten 'ABA 72 South Bekasi, Bekasi City showed that the development of expressive language skills possessed by children aged 4-5 years through storytelling one day one book experienced a significant increase.